Conservative oxygen therapy in critically ill and perioperative period of patients with sepsis-associated encephalopathy - Li, Yun; Zhao, Lina; Yu, Yang; Zhang, Kai; Jiang, Yi; Wang, Zhiwei; Xie, Keliang; Yu, Yonghao (Frontiers in Immunology, 2022)
Objectives Sepsis-associated encephalopathy (SAE) patients in the intensive care unit (ICU) and perioperative period are administrated supplemental oxygen. However, the correlation between oxygenation status with SAE and the target for oxygen therapy remains unclear. This study aimed to examine the relationship between oxygen therapy and SAE patients. Methods Patients diagnosed with sepsis 3.0 in the intensive care unit (ICU) were enrolled. The data were collected from the Medical Information Mart for Intensive Care IV (MIMIC IV) database and the eICU Collaborative Research Database (eICU-CRD) database. The generalized additive models were adopted to estimate the oxygen therapy targets in SAE patients. The results were confirmed by multivariate Logistic, propensity score analysis, inversion probability-weighting, doubly robust model, and multivariate COX analyses. Survival was analyzed by the Kaplan-Meier method. Results A total of 10055 patients from eICU-CRD and 1685 from MIMIC IV were included. The incidence of SAE patients was 58.43%. The range of PaO2 (97-339) mmHg, PaO2/FiO2 (189-619), and SPO2≥93% may reduce the incidence of SAE, which were verified by multivariable Logistic regression, propensity score analysis, inversion probability-weighting, and doubly robust model estimation in MIMIC IV database and eICU database. The range of PaO2/FiO2 (189-619) and SPO2≥93% may reduce the hospital mortality of SAE were verified by multivariable COX regression. Conclusions SAE patients in ICU, including perioperative period, require conservative oxygen therapy. We should maintain SPO2≥93%, PaO2 (97-339) mmHg and PaO2/FiO2 (189-619) in SAE patients.